TERPILIHNYA FIGUR MINORITAS DALAM MASYARAKAT MAJEMUK BELOTO KABUPATEN FLORES TIMUR: TINJAUAN PERSPEKTIF TEORI PENGARUH MINORITAS DAN TEORI KONTAK - Abdurrahman, Abdurrahman; Al-Banjari, M. Husin; Muradi, Muradi (Al-Ijtima`i: International Journal of Government and Social Science, 2019)
Election of Beloto village head East Flores District 2015 is a paradox in modern-pragmatic political logic, where Solhan Masang, who was the personification of the Muslim minority group, was chosen as the head of Beloto village in the middle of the majority of Catholic communities. The Beloto community practices village head elections in accordance with the principles and spirit of democracy. The decision to choose Solhan Masang as the Village Head, the Beloto community does not take into account the brand of religion, ethnicity, group or group what the candidate is as a uniform political calculation with the majority of the people as long as the political drama of the election is presented. This reason is why this research needs to be conducted to explore this healthier political phenomenon more deeply in Beloto Village. There are two theories that I use in analyzing this phenomenon, namely, first, the theory of minority influence, this theory approach emphasizes 3 (three) components that minority figures must have, namely attitudes of consistency, confidence (self-confidence) and persuasive. Second, contact theory, this theory emphasizes more interaction between individuals and minority groups and the majority are bound by a condition that must be fulfilled